Some anatomical, morphological and physiological features of the flag leaf in introgressive bread wheat lines with Aegilops columnaris Zhuk. genetic material - Iu. V. Dashtoian; A. V. Kalinina (Труды по прикладной ботанике, генетике и селекции)
Background. A study of morphological, anatomical and physiological parameters of plants obtained as a result of introgressive breeding is important for assessing the prospects of their further use.   Materials and methods. Spring bread wheat plants of cv. ‘Dobrynya’ and a set of introgressive wheat lines with Аegilops columnaris Zhuk. genetic material were studied. The area of flag leaves was measured. Preparations of macerated leaf tissue were used to analyze mesophyll parameters. Spectrophotometric techniques were applied to determine the composition of photosynthetic pigments in the flag leaf.   Results and conclusion. A negative effect of substitutions of chromosomes 2A, 5B, 6A and 6D for chromosomes of the U and X genomes on the size of the flag leaf area was disclosed. There were no significant differences in cell shape and size among the lines and in comparison with the recipient cultivar. Changes in the content of pigments in flag leaf laminae have been recorded. Increased content of all groups of pigments was observed in the lines containing substitutions 6A(6G), 6B(6X) and 5B(5X)6A(6X). Substitution 2A(2U) led to a decrease in the level of chlorophyll, the ratio of chlorophyll a to b, and the ratio of chlorophyll to carotenoids.